Ethical and legal race-responsive vaccine allocation - Steuwer, Bastian (Bioethics, 2023)
In many countries, the COVID-19 pandemic varied starkly between different racial and ethnic groups. Before vaccines were approved, some considered assigning priority access to worse-hit racial groups. That debate can inform rationing in future pandemics and in some of the many areas outside COVID-19 that admit of racial health disparities. However, concerns were raised that “race-responsive” prioritizations would be ruled unlawful for allegedly constituting wrongful discrimination. This legal argument relies on an understanding of discrimination law as demanding color-blindness. We argue that a, color-blind understanding of discrimination would be hostile only to one of two rationales for prioritizing the relevant racial minorities in settings of racial health disparities. We also propose a method for incorporating appropriate race-responsive concerns that is in many ways ethically and legally superior to ones suggested thus far. That method turns artificial intelligence, thanks precisely to its artificial and “black box” nature (features that underlie recent concerns about artificial intelligence's discriminatory potential), into an instrument of social justice.